The Dialectics of Political and Administrative Rationality in the Deliberative Process of Village Development Planning - Franky Djafar; Rifka S. Akibu (Jurnal Ilmu Administrasi Negara AsIAN (Asosiasi Ilmuwan Administrasi Negara), 2025)
This study analyzes the dialectic between political and administrative rationality in the deliberative development planning process in Pentadio Timur Village, Gorontalo Regency. The village planning process is often in tension between political interests (the aspirations of residents and local elites) and administrative rationality (rules, data, and technocratic procedures). Using a qualitative approach and case study method, this study explores the dynamics of the Village Development Planning Meeting (Musrenbangdes) as a deliberation space between political and administrative actors. The results show that political rationality plays a crucial role in maintaining the social legitimacy of village government, while administrative rationality ensures program efficiency, accountability, and sustainability. When both are able to interact collaboratively, the deliberative process produces planning that is inclusive and adaptive to community needs. However, the imbalance between these two rationalities remains a challenge, primarily due to the limited technical capacity of the apparatus and the influence of electoral interests.